The Military Factor in Nigeria’s Fourth Republic: Implications for Future Democracy - OLUBIYO, Kolade G.; OWOLABI, Oladunni; KUTU, Augustine Adebayo (Journal of Posthumanism, 2025)
This study examines the significant involvement of the military in Nigeria’s democracy, focusing on its implications for democratic consolidation and stability. The Fourth Republic in Nigeria continues to witness profound military participation in democratic governance. Although there is a constitutional provision empowering the military to protect the nation’s territorial integrity against external aggression and to suppress internal insurrection, when necessary, Nigeria’s democratic experience has seen the military addressing civil matters that fall under the jurisdiction of the police and other paramilitary security forces. In many instances, the military has become a tool for executive officials who have used it to perpetuate undemocratic practices. The Odi and Zaki-Biam incidents, the imposition of emergency rule in certain states, the suspension of elected officials, the deployment of military personnel for election duties, the suppression of peaceful protests, and the enforcement of orders are all clear examples of impunity and military overreach. This study is based on qualitative research methods and draws from secondary sources, mainly published academic literature. The core of our argument is that Nigeria’s democracy is a consequence of prolonged military rule, which has ingrained a culture of impunity and despotism into the societal fabric, thereby undermining democratic institutions. While the military has continued to assume a messianic role in stabilizing democracy, the institution has ironically been the architect of the country’s democratic failures. Hence, military’s deep involvement will continue to pose a significant threat to democratic stability and consolidation.